TEATER TRADISIONAL DI SURABAYA 1950-1965: RELASI MASYARAKAT DAN ROMBONGAN SENI - . Samidi (Humaniora, 2006)
This article intends to study the relation between social spectators and the troupe of theatre in Surabaya. The spectators were needed in traditional performance because the presence of spectators was related to the fund raising. Spectators were related to fund. Troup of theatre was basically commercial and so the spectators had significant function in providing financial support to members of he troupe. Most of the people of Surabaya liked theatre, such as ludruk and wayang wong. Both ludruk and wayang wong had to make their admirers and fans happy and at the same time obey the instructions and regulations of the local government.